THE INFLUENCE OF GLOBALIZATION ON LAND OWNERSHIP IN INDONESIA IN TERMS OF PERSPECTIVE SOCIOLOGY OF LAW - Hamler Hamler; Yulia Mirwati (PENA LAW: International Journal of Law, 2022)
The influence of globalization on land ownership in Indonesia, viewed from the perspective of legal sociology, is the difficulty for people to obtain land ownership in urban areas. This is not due to bureaucracy but rather the influence of urban and preeconomic progress in the city center so that the land for residential houses is getting narrower (exhausted) and left out. The challenge ahead for the Indonesian nation in terms of legal sociology in responding to the influence of globalization, especially economic globalization on land ownership is not to make land a business commodity because it is supported by easy land ownership registration services so that land with clear legal status becomes easy to trade and get economic benefits even though these benefits are only temporary.